2021
DOI: 10.3389/fmicb.2021.712260
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Association of Viral Dynamics With Disease Severity Depending on Patients’ Age Group in COVID-19

Abstract: Despite a clear association of patient’s age with COVID-19 severity, there has been conflicting data on the association of viral load with disease severity. Here, we investigated the association of viral load dynamics with patient’s age and severity of COVID-19 using a set of respiratory specimens longitudinally collected (mean: 4.8 times/patient) from 64 patients with broad distribution of clinical severity and age during acute phase. Higher viral burden was positively associated with inflammatory responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…13 The results can also vary depending on host factors, for example one study reported a positive correlation of viral load with disease severity in younger age groups (<60 years), but not in older ones. 23 However, a more consistent association between higher viral load and disease severity is found in cohorts of hospitalized patients 13,15,16,24 such as ours, although not always in multivariate analysis. 18 This was also observed during the previous SARS-CoV epidemic, where Chu et al showed that high viral load at hospital admittance was independently associated with more severe forms of SARS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…13 The results can also vary depending on host factors, for example one study reported a positive correlation of viral load with disease severity in younger age groups (<60 years), but not in older ones. 23 However, a more consistent association between higher viral load and disease severity is found in cohorts of hospitalized patients 13,15,16,24 such as ours, although not always in multivariate analysis. 18 This was also observed during the previous SARS-CoV epidemic, where Chu et al showed that high viral load at hospital admittance was independently associated with more severe forms of SARS.…”
Section: Discussionsupporting
confidence: 73%
“…Comparison between these studies is difficult as they vary to a large extent with regards to cohort composition, study design, sampling time‐points after onset of symptoms and sample selection 13 . The results can also vary depending on host factors, for example one study reported a positive correlation of viral load with disease severity in younger age groups (<60 years), but not in older ones 23 . However, a more consistent association between higher viral load and disease severity is found in cohorts of hospitalized patients 13,15,16,24 such as ours, although not always in multivariate analysis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis to explain these observations is that the B.1.1.7 variant causes a higher viral load [ 40 ] as compared to previously circulating variants, but that the positive correlation between viral load and disease severity is only observed in younger patients. Indeed, it has been shown that respiratory viral loads were generally correlated with inflammatory responses in younger patients, but less correlated with those in older patients [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“… 102 , 103 , 104 This model also explains, why the prognosis of COVID‐19 is worse in males, where TMPRSS2 expression is higher, 105 and why biomarkers of the inflammatory response show a higher dispersion in critical cases of COVID‐19. 106 , 107 …”
Section: Systemic Physiology and Pathologymentioning
confidence: 99%
“…The modelling strategy of templates and anchors can be subdivided into distinct although often overlapping conceptual steps. The following steps of systemic conceptualisation of COVID‐19 as an epistemic object appear to be useful 106 , 120 : assemble a transdisciplinary group of experts; define the boundary structure of the system; collect observations and data, ideally within informational contexts; establish the organisational levels of analysis; for the overall template model, and for each potential anchor, identify the key drivers and their networks of interrelationships; perform analyses at each layer, some of which may be detailed and others quite coarse, due to the availability or lack of data; assess interactions of anchor models at the same level; use input–output relationships of all anchor models of a given level to provide information for the model(s) at next higher level; assess reasonableness of the integration of information at the next higher level; validate the model, as far as possible, by testing the effects of low‐level inputs on the overall responses of the template model; replace fixed parameters with ranges of possible values and explore consequences, for instance, through Monte‐Carlo simulations; test and validate the model with new data, especially from real‐world situations (see Section 1.3 ). …”
Section: Systems Thinking As Thought Culturementioning
confidence: 99%